Characterization, swelling behavior and field evaluation of oil palm empty fruit bunch based superabsorbent polymer composites - Shafinaz Jamaludin, 1985-; Shahrir Hashim; Fakulti Kejuruteraan Kimia (2010)
Thesis (Sarjana Kejuruteraan (Polimer)) - Universiti Teknologi Malaysia, 2010